Pelaksanaan Program Praktek Kerja Industri Dalam Penguasaan Kompetensi Keahlian Administrasi Perkantoran - Lisnawati, Rika; Adman, Adman (Universitas Pendidikan Indonesia, 2019)
This research is motivated by low level of competency skill of Office Administration skill by learner on Office Administration. The purpose of this study is to obtain a description of the effectiveness of the implementation of industrial work programs, obtain a description of the level of control of the competence of office administration expertise by learners, and to determine whether there is influence from the effectiveness of the implementation of industrial work programs to mastering the competence of administrative office skills by participants educate. This study uses a quantitative approach. The research method used is explanatory survey method. Data collection techniques were conducted through questionnaires. Members of the sample are 58 learners who have implemented prakerin program on Office Administration. Data analysis technique used in this research is simple linear regression test. Based on the results of research, obtained information that the implementation of industrial work programs in the category of very effective and control of the competence of office administration by students are in the high category. In addition, the results of the study prove that there is a positive and significant influence between the effectiveness of prakerin implementation to the mastery of the competence of office administration expertise by the learners of 17.78% in the Office Administration. Based on the results of the research, the authors suggest that the parties involved in the implementation of prakerin maintain and or improve the effectiveness of prakerin implementation in order to improve the mastery of the competence of administrative skills of the Office by the learners, especially in the supervision and guidance by the school / industry supervisor / mentor to the participants educated during prakerin implementation.ABSTRAKPenelitian ini dilatarbelakangi rendahnya tingkat penguasaan kompetensi keahlian Administrasi Perkantoran oleh peserta didik pada Program Keahlian Administrasi Perkantoran. Tujuan dari penelitian ini adalah untuk memperoleh gambaran mengenai efektivitas pelaksanaan program praktek kerja industri, memperoleh gambaran mengenai tingkat penguasaan kompetensi keahlian administrasi perkantoran oleh peserta didik, dan untuk mengetahui apakah ada pengaruh dari efektivitas pelaksanaan program praktek kerja industri terhadap penguasaan kompetensi keahlian administrasi perkantoran oleh peserta didik. Penelitian ini menggunakan pendekatan kuantitatif. Metode penelitian yang digunakan adalah metode survey eksplanasi. Teknik pengumpulan data dilakukan melalui kuesioner. Anggota sampel yaitu 58 peserta didik yang sudah melaksanakan program prakerin pada Program Keahlian Administrasi Perkantoran. Teknik analisis data yang digunakan dalam penelitian adalah uji regresi linier sederhana. Berdasarkan hasil penelitian, didapatkan informasi bahwa pelaksanaan program praktek kerja industri berada pada kategori sangat efektif dan penguasaan kompetensi administrasi perkantoran oleh peserta didik berada pada kategori tinggi. Selain itu, hasil penelitian membuktikan bahwa terdapat pengaruh yang positif dan signifikan antara efektivitas pelaksanaan prakerin terhadap penguasaan kompetensi keahlian administrasi perkantoran oleh peserta didik sebesar 17,78% pada pada Program Keahlian Administrasi Perkantoran. Berdasarkan hasil penelitian, maka sarannya adalah agar pihak-pihak yang terlibat dalam pelaksanaan prakerin mempertahankan dan atau meningkatkan efektivitas pelaksanaan prakerin guna meningkatkan penguasaan kompetensi keahlian Administrasi Perkantoran oleh peserta didik terutama dalam aspek pengawasan dan bimbingan oleh tenaga/pembimbing dari pihak sekolah dan industri terhadap peserta didik selama pelaksanaan prakerin.